Cover Image, Volume 86, Issue 10. Issue 10 (16th November 2018) - Kuldyushev, Nikita A.; Mineev, Konstantin S.; Berkut, Antonina A.; Peigneur, Steve; Arseniev, Alexander S.; Tytgat, Jan; Grishin, Eugene V.; Vassilevski, Alexander A.
Abstract : Reverse Cover : The cover image is based on the Structure Note Refined structure of BeM9 reveals arginine hand, an overlooked structural motif in scorpion toxins affecting sodium channels by Nikita A. Kuldyushev et al., DOI:https://doi.org/10.1002/prot.25583 .